Bagaimana HOTS siswa dengan E-modul Fisika Terintegrasi Kearifan Lokal dan Aplikasi Android? - Muhammad Zaini; Muhamad Zohri; Lia Saptini Handriani; Muhammad Kafrawi; Musanni (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to evaluate the feasibility and effectiveness of the gendang beleq integrated e-module with the concept of vibration and waves that have been developed. This study is a development research with a 4D model, which is one of the media development models with the stages of define, design, develop, and disseminate. The effectiveness test of the e-module uses the t-test on SPSS 24, which is a popular statistical tool used in research. The population of the study was students of class XI IPA at SMAN 5 Mataram and the sample was students of class XI IPA 1, 2, 3, and 4. The average value of media validation was 4.8 (very valid) and learning validation was 4.7 (very valid) with a Likert scale of 5. Based on these results, the developed e-module is feasible to use. The results of the effectiveness test showed a sig value of 0.000 <0.05, Partial Eta Squared 0.994, and the average of the experimental and control classes were 80.32 and 75.81. These data show that the use of the developed e-module is effective in improving students' HOT such as analyzing, evaluating, and creating.